Determinants of Telemedicine Adoption Among Patients (Proceeding International Collaborative Conference on Multidisciplinary Science, 2024)
The rapid advancement of technology has positioned telemedicine as a vital tool for enhancing healthcare accessibility, particularly for underserved populations. This study aims to identify the key determinants influencing telemedicine adoption from the patient's perspective, focusing on three critical factors: patient satisfaction, technology usability, and healthcare accessibility. Utilizing a quantitative research design, the study was conducted in the Davao Region, Philippines, employing descriptive-correlational and causal-comparative methodologies to analyze relationships and potential predictors of telemedicine adoption. Data were collected through four adapted questionnaires measuring the aforementioned variables, ensuring a reliable assessment of patient experiences. The findings reveal that healthcare accessibility is the most significant predictor of telemedicine adoption (p < 0.05), explaining 67.5% of the variance in usage, while patient satisfaction and technology usability did not demonstrate statistical significance. These results emphasize the importance of improving access to telemedicine services to enhance patient engagement and overall satisfaction. Furthermore, they indicate that while usability and satisfaction are relevant, they must be accompanied by increased accessibility to drive adoption effectively. This study contributes to the existing literature by shifting the focus from purely technical aspects of telemedicine to more patient-centered factors, highlighting the need for ongoing research into the barriers and facilitators affecting telemedicine utilization. Addressing these insights can aid healthcare providers and policymakers in developing strategies that better meet the needs of diverse patient populations, ensuring equitable access to healthcare services through telemedicine.